Language and Poetic Language - Abdul Maruf Brzinji, Othman (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
It has been acknowledged that the language is one of the main pillars of a nation with which the nation will be distinguished from the others. Mean-while poetic language merges from the womb of the everyday language which becomes the identity of enlightenment and development of the culture and literature The research will be as follows: The first section: is devoted to giving the definition functions, and the notions of language. This section is divided in to two subsections: The first one is specified to the notion and the definition of language. Whereas the second subsection is devoted to discuss the functions of language. The second section: highlights the poetic language, the characteristics, roles, and the importance of language in poetry. This section is divided in to subsections: The first one is specified to identity the poetic language in terms of its characteristics. The second subsection refers to the role and the importance of poetic language.